HAUGHT, J. F., Christianity and Science. Toward a Theology of Nature - Sequeiros, L. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
(Orbis Books, New York, 2007). 208 pp. ISBN:978-1-57075-740-2. 23 × 15 cm.